2014
DOI: 10.1002/imhj.21437
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of White and Hispanic Women's Stories of Adjustment to the Birth of a Child

Abstract: As part of a larger project designed to inform prevention and treatment of postpartum depression and promote positive mother-child relationships in diverse families, this study describes personal stories of postnatal adjustment from 14 White and 9 Hispanic women recruited from prenatal care clinics. Qualitative interviews conducted in the mothers' primary language (English or Spanish) were analyzed using a modified grounded theory content-analysis approach. The coding scheme developed to capture the women's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…this process, her role and occupational identity change in the relationship with her partner, her professional or employment domain, her social domain and her self-identity. [34,35] 'Baby blues' , usually starting on the third day after delivery, are experienced by up to 80% of women globally, primarily as a result of the hormonal and physiological changes during and after the birth process, and characterised by tearfulness, fatigue, anxiety, high emotionality, low spirits and muddled thinking. [36,37] The symptoms of baby blues last from a few hours to 2 weeks after delivery, with a reported 20% of mothers experiencing them going on to develop depression.…”
Section: Researchmentioning
confidence: 99%
“…this process, her role and occupational identity change in the relationship with her partner, her professional or employment domain, her social domain and her self-identity. [34,35] 'Baby blues' , usually starting on the third day after delivery, are experienced by up to 80% of women globally, primarily as a result of the hormonal and physiological changes during and after the birth process, and characterised by tearfulness, fatigue, anxiety, high emotionality, low spirits and muddled thinking. [36,37] The symptoms of baby blues last from a few hours to 2 weeks after delivery, with a reported 20% of mothers experiencing them going on to develop depression.…”
Section: Researchmentioning
confidence: 99%
“…A dimension of quantity (counts/frequency) is rendered in terms of subjective ownership of instrumentality in a sport team’s victory or defeat. Similarly, in an example of quantitizing, Pollard, Nievar, Nathans, and Riggs (2014) counted the frequency of occurrences of various themes from qualitative narratives and concluded that based on nonsignificant chi-squared analyses that the experiences of Hispanic and Caucasian mothers did not differ thematically. In this example, a quantitative rubric is utilized to make claims regarding dimensions of experience.…”
Section: Defining Quantitative and Qualitative Domains And Approachesmentioning
confidence: 99%
“…Like some other family stress theories (family distress model, Cornille & Boroto, 1992; family adjustment and adaptation response model, Patterson, 2002), the double ABCX model incorporates two stages of processes related to ultimate family functioning, which also includes resources and subjective perceptions. The double ABCX model is versatile enough to be applied toward understanding the impact of various stressful family circumstances including child birth (Pollard et al, 2014), divorce (Plunkett et al, 1997), remarriage (Crosbie‐Burnett, 1989), home‐based stroke rehabilitation (Clark, 1999), grandparents parenting grandchildren (Bailey et al, 2009), and especially the raising of children with special needs (e.g., Bohanda et al, 2019; Han et al, 2018; Pakenham et al, 2005; Payneter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%